KONSEP MUDHARABAH Antara Kajian Fiqh dan Penerapan Perbankan - Masse, Rahman Ambo (DIKTUM: Jurnal Syariah dan Hukum, 2010)
This article tries to study how the concept of mudharabah in classical Islamic legal theories implemented in Islamic monetary institution, especially Islamic banking. Using library research, this study shows that there exists discrepancy between the concept of mudharabah in classical Islamic books and its implementation in Islamic banking. The discrepancy indicates that the door of ijtihad is still widely open in contemporary Islamic law. The prudential principle necessitates Islamic banking to contextualize the classical concept of mudharabah in contemporary socio-cultural situation.